Perception of vocational school students towards online learning and their TOEIC scores - Wijayanti, Putu Ranti; Suwartono, Tono; Kusuma, Lintang (International Journal for Educational and Vocational Studies, 2022)
This study aimed to know whether there was a correlation between students perception of online learning and their English achievement in the Test of English for International Communication (TOEIC). To achieve this objective, the study applied the quantitative method. There were 30 students from the third grade, at a vocational school in the district of Ajibarang, Banyumas Regency, Central Java, Indonesia, who became the sample of the research. To collect the data, this study used survey questionnaires and the student TOEIC scores, which was documented to assess the English proficiency progress over time during their study. Furthermore, the data analysis was conducted by multiple regressions using SPSS version 2. The result showed that 69% of students responses had a positive view of the online class. However, there was no significant correlation between the students perception of online learning they attended and their TOEIC score achievement.